MANAGEMENT OF PATIENTS WITH BREAST PATHOLOGY ACCORDING TO BI-RADS CLASSIFICATION - Zhumaeva D.R. (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Resume. To make a correct diagnosis, it is necessary to have diagnostic criteria that  make  it  possible  to  accurately  prescribe  treatment.  Modern  requirements  for diagnostic  methods  are  accuracy,  high  information  content,  and  accessibility.  The article  discusses  the  BI-RADS  (Breast  Imaging  Reporting  and  Data  System) international  system  for  describing  and  processing  mammography  and  ultrasound data, which has been gaining interest in our country in recent years. The BI-RADS system is a good tool for determining the algorithm of management of patients with breast diseases.